KiDS-450: the tomographic weak lensing power spectrum and constraints on cosmological parameters. Issue 4 (19th July 2017) - Köhlinger, F.; Viola, M.; Joachimi, B.; Hoekstra, H.; van Uitert, E.; Hildebrandt, H.; Choi, A.; Erben, T.; Heymans, C.; Joudaki, S.; Klaes, D.; Kuijken, K.; et al.
Abstract: We present measurements of the weak gravitational lensing shear power spectrum based on 450 ^2 of imaging data from the Kilo Degree Survey. We employ a quadratic estimator in two and three redshift bins and extract band powers of redshift autocorrelation and cross-correlation spectra in the multipole range 76 ≤ ℓ ≤ 1310. The cosmological interpretation of the measured shear power spectra is performed in a Bayesian framework assuming a ΛCDM model with spatially flat geometry, while accounting for small residual uncertainties in the shear calibration and redshift distributions as well as marginalizing over intrinsic alignments, baryon feedback and an excess-noise power model. Moreover, massive neutrinos are included in the modelling. The cosmological main result is expressed in terms of the parameter combination S_8 σ _8 Ω _m/0.3 yielding S 8 = 0.651 ± 0.058 (three z-bins), confirming the recently reported tension in this parameter with constraints from Planck at 3.2σ (three z-bins). We cross-check the results of the three z-bin analysis with the weaker constraints from the two z-bin analysis and find them to be consistent. The high-level data products of this analysis, such as the band power measurements, covariance matrices, redshift distributions and likelihood evaluation chains are available at http://kids.strw.leidenuniv.nl .